THE EFFECTIVENESS OF SPECIAL ECONOMIC ZONES IN INVESTMENT ATTRACTION (International Congress on Economics, Management and Business Studies, 2026)
In the context of modern globalization, investment emerges as a critical strategic factor in ensuring national economic stability, expanding productive capacity, and enhancing international competitiveness. In particular, attracting Foreign Direct Investment (FDI) plays a pivotal role in technological modernization, the creation of new production facilities, the promotion of innovation activities, and the generation of employment opportunities. From this perspective, Special Economic Zones (SEZs) are widely utilized in global practice as effective institutional mechanisms for attracting investment.Special Economic Zones are designated geographic areas where specific economic, legal, customs, and administrative conditions are established to conduct business activities. Their primary objective is to stimulate investment activity, develop manufacturing capacity, and efficiently leverage the economic potential of regions. Incentives granted to investors within these zones—including tax reliefs, customs preferences, fully developed infrastructure, and streamlined administrative procedures—substantially enhance the attractiveness of investment projects.